On the Production of Climate Information in the High Mountain Forests of Guatemala. Issue 2 (4th March 2017) - Pons, Diego; Taylor, Matthew J.; Griffin, Daniel; Castellanos, Edwin J.; Anchukaitis, Kevin J.
Abstract : Guatemala's population is dependent on cash crops and subsistence agriculture, the yield of which depends on both the timing and quantity of rainfall. Detailed knowledge about Guatemala's past, current, and future climate is therefore critical to the well-being of a country so reliant on agriculture. Relatively little information about Guatemala's climate exists, though, due to sparse instrumental records and limited high-resolution paleoclimate data. Given this situation, the development of climate data is the necessary first step toward facilitating improved decision making and robust adaptation in the face of predicted future climate change. Here we document how we successfully used tree rings to produce an annually resolved paleoclimate record from Guatemala stretching back to the late seventeenth century. These data provide a more comprehensive understanding of the range of natural variability in local and regional hydroclimate. This increased understanding could then be used to generate locally relevant climate information, to assist in planning, and toward reducing climate-related vulnerability at regional to local scales in agriculturally dependent communities. Our goal herein is to begin to close the gap between climate data generation and the use of relevant agrometeorological information in Guatemala by identifying key participants, decision makers, and modes of stakeholder engagement that are critical to coproduce climate information in the mountain regions of Guatemala.